Intra-articular Injection of a Vital Micrograft Combined With a Metabolic Solution for Knee Osteoarthritis: A Case Report on Novel Two-Phase Regenerative Treatment - Svolacchia, Fabiano; Svolacchia, Lorenzo (Scripta Medica, 2025)
Knee osteoarthritis (OA) is a prevalent degenerative joint disorder characterised by the gradual deterioration of the protective cartilage in the knee with limiting treatment options. A 55-year-old male with symptomatic knee osteoarthritis underwent a novel two-phase regenerative treatment combining micro-fragmented adipose tissue injection with metabolic solution infiltration. The patient presented with medial and anterior knee pain (visual analogue scale - VAS 4.5, knee injury and osteoarthritis outcome score - KOOS 64 %). Treatment involved intra-articular injection of 30-40 micron microfiltered adipose tissue followed by a solution containing non-cross-linked hyaluronic acid, branched amino acids and sodium bicarbonate to activate membrane glycoproteins and drive adipose-derived stem cells (ADSCa) to exosome budding. At six months, dramatic improvement was observed with VAS decreasing to 0.5 and KOOS increasing to 95 %. No adverse reactions occurred. This minimally invasive technique represents a promising approach for early-stage knee osteoarthritis treatment.
Keywords: Osteoarthritis; Stem cells, adipose-derived; Regenerative medicine; Knee joint; Adipose tissue, microfiltered; Exosomes